In-situ X-ray difraction analysis of reverted austenite in supermartensitic stainless steel weld deposits - Zappa Maidana, Norberto Sebastián (2022)
To improve the mechanical properties in supermartensitic stainless steel weld deposits, suitable post weld heat treatments (PWHT) are required, since these properties are controlled by the resulting microstructure. Some aspects of localized corrosion resistance could also be enhanced by the PWHT. In this sense, the austenite transformation or stability is a key issue. The aim of this work is to “in-situ” analyze the evolution of austenite during the thermal cycle associated to a post weld inter-critical heat treatment in a supermartensitic stainless steel weld deposit, by means of a thermomechanical simulator integrated on a synchrotron X-ray diffraction line. An all-weld metal coupon was welded with a semi-automatic process. Dilatometry measurements were performed at different heating rates (1, 10 and 100 K/s) in the thermomechanical simulator, to determine the critical transformation temperatures (Ac1 and Ac3) of the all-weld metal. To study the phase transformation during the applied thermal cycle (heating to 938 K at 1 K/s, maintenance during 15 min and cooling to room temperature at 2 K/s), in-situ synchrotron X-ray diffraction measurements were carried out in the facilities of National Laboratory Synchrotron Light (Campinas, Brasil). The microstructural evolution was discussed in terms of volumetric phase fractions, micro-deformation and crystallite size. The techniques used allow to detect the critical transformation temperatures, phase transformations and their kinetics, monitoring particularly the austenite evolution during the post weld heat treatment cycle. At the inter-critical temperature 71% of austenite was formed, after the 8.5 min from the 15 min of permanence. Finally, at room temperature 29% of stable reverted austenite was obtained. Both martensite and austenite there did not show significant variations during the thermal cycle both for microstrain and crystallite size.